Creating a new socio-technical regime in China: Evidence from the Sino-Singapore Tianjin Eco-City. (June 2015) - Hu, Mei-Chih; Wu, Ching-Yan; Shih, Tommy
Highlights: A hub-and-spoke model for China's urbanization. China's goal of achieving socio-technical transformation by eco-urbanization. The example of the Sino-Singapore Tianjin Eco-City. Technologies for urban transport, energy, water supply, and waste treatment. Smart city systems management. Abstract: The Sino-Singapore Tianjin Eco-City (SSTEC) in China was designed to leverage Singaporean expertise in top-down city planning, systematic management, and water treatment technologies and act as a replicable hub-and-spoke model. This study shows that an expansion of the scale of urbanization, and its transformation into the focal point of the hub-and-spoke eco-city model will enable China to advance as an international pioneer, by the creation of a new socio-technical regime dependent on green and ecologically sustainable systems. In particular, the potential capacity of China's new socio-technical regime, built on eco-cities, is based on its capability to (1) create a vision for a smart energy system; (2) drive down the cost of renewable energy equipment and devices; (3) support local industrial clusters for socio-economic development; (4) implement effective policies for city-level solutions; and (5) standardize and replicate these strategies in the new regime as a whole. In the top-down landscape approach, the public authority's integrated administrative capability and capacity is important as a means by which to link the various types of stakeholders. This has to be done, in the process of managing a city's transition and reducing the risk of transformational failure, by reinforcing the four types of capital assets – namely manufacturing capital, natural capital, human capital, and social capital.